Peta Risiko Diabetes Melitus di Jawa Barat Tahun 2019-2023 dengan Pemodelan Spatio-Temporal - Venita Syavera; Muhamad Syazali (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2024)
Diabetes Mellitus (DM) is a serious global health issue, caused by decreased insulin production by the pancreas. Poor dietary habits, obesity, smoking, mental stress, lack of physical activity, and high blood pressure are risk factors that contribute to the DM. This study aims to map the relative risk of DM in West Java from 2019 to 2023, which will provide spatial and temporal patterns of DM distribution, which can be used for the development of effective prevention and management strategies by policy makers. DM risk mapping was carried out using the spatio-temporal Conditional Autoregressive (CAR) method, utilizing the CARBayesST package available in Rstudio. The relative risk of DM varies across districts/cities. In 2019, areas with high relative risk included Karawang Regency, Ciamis Regency, Sukabumi Regency, Bekasi Regency, Sumedang Regency, and West Bandung Regency. Over time, a decreasing trend in relative risk was seen in many areas, although some areas still showed high relative risk above the expected value in 2023, Sumedang Regency and West Bandung Regency. The results of this study indicate the need for more effective DM prevention and management strategies, especially in high-risk areas.